The irresistible introvert : harness the power of quiet charisma in a loud world - Chung, Michaela (Skyhorse Publishing, 2016)
"Learn the tools to shed your mask of extroversion, develop your own magnetism, and reveal the true you. One third to one half of Americans are introverts in a culture that celebrates-even enforces-an ideal of extroversion and a cult of personality. Political leaders are charismatic, celebrities bask in the spotlight, and authority figures are assertive. It is no surprise that a "quiet revolution" has begun to emerge among the "invisible" half of the population, asserting that they are just as powerful in their own unique ways. The Irresistible Introvert embodies the spirit of this revival and breaks down the myth that charisma is reserved for extroverts only. This mini manifesto shows introverts how to master the art of quiet magnetism in a noisy world-no gregariousness required! Within these pages, you'll discover how to shed the mask of extroversion and reveal a more compelling (and authentic) you. You'll also learn how to: [dot below] Master the inner game of intrigue [dot below] Manage your energy for optimal engagement [dot below] Create an emotional ecosystem for charisma [dot below] Establish introverted intimacy [dot below] Cultivate communication skills for quiet types As a "professional" charismatic introvert, author Michaela Chung demonstrates that you no longer have to forcefully push yourself outward into the world against your nature, but can rather magnetize people inward toward the true you. In the process, you'll learn to embrace your "innie life" and discover potential you never knew you had"--